Reframing History: New Historicism in Cinematic Critique of World War II Perspectives in 'The Fighter Pilot' (2013) and 'Saving Private Ryan' (1998) - Tano, Andreas; Simanjuntak, Immanuel Sheva (Jurnal Pendidikan Makarios, 2024)
This study aims at showing the biases of two contrast movies, ‘The Fighter Pilot’ on the Japanese side and ‘Saving Private Ryan’ on the American side in the context of New Historicism. Having the two movies analyzed, the New Historicism theory by Stephen Greenblatt (2011) was used to reveal the motives of both works. Two contextual aspects of the narratives were contrasted, ‘Idealized Image" vs. Realism’. Hence, the cinematography aspects of both movies were also analyzed to reveal the emotional impacts and the motives of the characters. As a result: 1) Emphasizing the themes of sacrifice, friendship, and loyalty, "The Fighter Pilot" presents an idealized image of Japanese fighter pilots during WWII, romanticizing their heroism, sacrifices, and positive qualities. 2) The portrayal of the American soldiers in the ‘Saving Private Ryan’ shows an idealized image of virtuous, patriotic, and brave individuals dedicated to duty, peacekeeping, and sacrifice for the greater good, using cinematic techniques to enhance heroism, while depicting the chaos and horrors of war, including the emotional toll on soldiers and moral dilemmas in the same era. 3) Both movies avoid depicting unpleasant scenes of WWII, contributing to a one-sided perspective that compromises the historical accuracy by selectively portraying narratives to fit a particular motive. Thus, historical movies can be a tool for shaping one’s perspective on historical events either to remember or to forget certain occurrences.